Interações alimentares entre o Boto-cinza, Sotalia Guianensis (Cetacea: Delphinidae - Van Beneden, 1864), e aves marinhas no complexo estuarino de Paranaguá, Paraná, Brasil - Machado, Lorena de Freitas (2012)
CHAPTER I: Paraná s coast was classified as extremely important for the conservation of seabirds in Brazil, with a record of ten to fourteen aquatic bird species in the Estuarine Complex of Paranaguá. This study aimed to evaluate how the area is used by aquatic birds, the daily and seasonal patterns of sightings and the influence of environmental factors (wind intensity and sea state) in the occurrence patterns of five aquatic birds species among the most frequent in the region: neotropical cormorants, Phalacrocorax brasilianus; gulls, Larus dominicanus; frigatebirds, Fregata magnificens; brown boobies, Sula leucogaster, and terns (Sternidae family). The observations were made during the four seasons of the year, spring of 2010 and summer, autumn and winter of 2011, from land-based points in Guaraqueçaba and Peças Island, totaling 400 hours of sampling effort, 260 hours in Guaraqueçaba (65 hours per season) and 140 hours in Peças Island (35 hours per season). In general, aquatic birds abundance was similar in both areas considering the average frequency of sighting. However, the most frequently sighted species differed between areas throughout the year. The daily pattern of aquatic birds occurrence was distinct in Guaraqueçaba and Peças Island. In both regions the higher frequencies of sighting occurred in cold seasons. Environmental parameters, wind and sea, were correlated with the frequency of aquatic birds sightings only in Guaraqueçaba and influenced differently the recorded bird species. CHAPTER II: Interactions between cetaceans and seabirds are common and involve different species around the world. This study aimed to characterize the interactions between guiana dolphins (Sotalia guianensis) and seabirds in Guaraqueçaba and Peças Island, two regions of the Estuarine Complex of Paranaguá, and test the hypothesis that: ecological parameters of the interactions differ between the two regions; the occurrence of interactions is related to specific environmental characteristics; the frequency / duration of the interactions vary with the seasons and seabirds species involved and these are related to physical and oceanographic variables. The observations were made during the four seasons of the year, spring of 2010 and summer, autumn and winter of 2011, from land-based points in Guaraqueçaba and Peças Island, totaling 400 hours of sampling effort, 260 hours in Guaraqueçaba (65 hours per season) and 140 hours in Peças Island (35 hours per season). Four seabird species were observed in interaction with the dolphins, brown boobies (Sula leucogaster), frigatebirds (Fregata magnificens), neotropical cormorants (Phalacrocorax brasilianus) and terns (Sternidae). The frequency of interactions varied according to the region and season. The interactions were more frequent in the afternoon at Peças Island and during flood tide in both regions. With respect to environmental parameters, intensity of wind and state of the sea, these were related to the interactions frequency only at Peças Island. The interactions observed in this study were characterized as commensalism, in which only the seabirds were benefited.